J-aggregates of meso-[2.2]paracyclophanyl-BODIPY dye for NIR-II imaging - Kang Li (Nature Portfolio, 2021)
J-aggregation has been proved to be an efficient strategy for the development of fluorescent imaging agents in the NIR-II spectral region but the design of appropriate J-aggregates is challenging. Here, the authors demonstrate J-aggregation of a BODIPY dye with NIR-II emission and demonstrate lymph node imaging for fluorescence guided surgery.